2005
DOI: 10.1007/s10493-004-1953-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of astigmatid mites using the second internal transcribed spacer (ITS2) region and its application for phylogenetic study

Abstract: The second internal transcribed spacer (ITS2) of nuclear ribosomal DNA from 73 specimens of Astigmata was analyzed by PCR amplification and DNA sequencing. The length of the ITS2 region varied from 282 to 592 bp. The interspecific variation based on consensus sequences was more than 4.1%, while the intraspecific or intra-individual variation was from 0 to 5.7%. The variation between geographically separated populations (0-3.2%) was almost the same as the variation within strains. The sequences of the ITS2 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…In the present study of A. ovatus, the length of the ITS2 sequences varied considerably (450 -490 bp). The results were consistent with studies reported by Noge et al (2005), in which a slightly higher intraspecific variation among the ITS2 sequences of A. ovatus was observed as compared to other astigmatid mites. Another reason was probably due to the ITS2 region of A. ovatus that was not homogenized completely within and/ or between individuals as been observed by Yang et al (2011).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study of A. ovatus, the length of the ITS2 sequences varied considerably (450 -490 bp). The results were consistent with studies reported by Noge et al (2005), in which a slightly higher intraspecific variation among the ITS2 sequences of A. ovatus was observed as compared to other astigmatid mites. Another reason was probably due to the ITS2 region of A. ovatus that was not homogenized completely within and/ or between individuals as been observed by Yang et al (2011).…”
Section: Discussionsupporting
confidence: 93%
“…The need for an expert taxonomist that requires skills and experience is a major drawback of this conventional method (Vargas et al, 2005). Moreover, several factors such as broken bodies, immature stages and closely morphological characters can also affect specific morphological identification (Colloff and Spieksma, 1992;Noge et al, 2005). The present study showed that the A. ovatus mite has its own morphological characteristics.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…After these qualityfiltering steps, the 401 762 retained sequences were further clustered at 98.0% sequence similarity as implemented in CD-Hit 4.6.1 (Fu et al, 2012). Compared with the routinely used 97%, this threshold is a better proxy at species level in several groups of fungi , protists (Litaker et al, 2007) and animals (Noge et al, 2005). Of 16 437 clusters, 6823 (41.5%) were represented by a single sequence.…”
Section: Molecular Analysesmentioning
confidence: 99%